Commenter la Thébaïde (16e-19e s.) : Caspar von Barth et la tradition exégétique de Stace - Berlincourt, Valéry. (Mnemosyne, Supplements, 2013)
Winner of the 2015 Jozef IJsewijn Prize for best first book on a Neo-Latin topic Early modern commentaries on Statius' Thebaid have been little studied; even that by Barth (1664-5), which holds a conspicuous place among them, has only been taken into account now and then, and often in a rather superficial way. The present book, which makes use of unpublished archival material, offers a comprehensive overview of these works (contexts, contents, interconnections). It is particularly interested in 16th-17th commentators and strives to give Barth's achievement the attention it deserves. By closely looking at the various ways in which the commentaries respond to Statius' poem, but also at the various kinds of discourse they present, it casts a new light on the reception of the Thebaid and on the early modern practice of commentary-writing. Les anciens commentaires imprimés de la Thébaïde de Stace ont été peu étudiés ; même celui de Barth (1664-5), qui occupe parmi eux une place éminente, n'a été pris en compte que de manière ponctuelle et souvent superficielle. Le présent ouvrage, étayé par des documents d'archives inédits, offre un examen général de ces travaux (contextes, contenus, filiations). Il s'intéresse particulièrement aux commentateurs des 16e-17e s. et s'efforce d'accorder à Barth l'attention qu'il mérite. En se penchant sur les différentes façons dont les exégèses répondent au poème de Stace, mais aussi sur les différents types de discours qu'elles présentent, il apporte un éclairage nouveau sur la réception de la Thébaïde et sur la pratique du commentaire au début de l'époque moderne.